A Study of Genetic Variability 30 Rice Genotypes (Oryza sativa L.) Using Some SSR (Simple Sequence Repeat) Markers Adrift Zn: Studi Variabilitas Genetik 30 Genotipe Padi (Oryza Sativa L.) Menggunakan Beberapa Marka SSR (Simple Sequence Repeat) Terpaut Zn - Pangaribuan, Tiwi Rumondang; Azizah, Elia; Susanto, Untung; Pramudyawardani, Furry; Prastika, Desi; Syafi’i, Muhammad (Talenta Publisher, 2022)
Rice is one of the important commodities in indonesia. Analysis of rice genetic diversity is necesarry for the succes of the local rice variety program. This study aims to identify the genetic variability and kinship patterns of 30 rice genotypes (Oryza sativa L.) using six zinc-linked SSR (Simple Sequence Repeat) markers. The research was conducted in September - December 2021 at the DNA Laboratory of the Sukamandi Rice Plant Research Center. A total of 30 local rice genotypes with diverse Zinc content have been analyzed using laboratory experiments. The results showed that there were different allele variations (2 – 8) among the genotypes tested with an average number of alleles of 4.5, while the average value of Polymorphism Information Content (PIC) amounted to 0.48 (0.20 - 0.70). 4 SSR markers have PIC values of > 0.5 (RM162, RM38, RM30, and RM80) which show that the markers are informative for the study of rice genetic diversity with Zinc content variety with an average gene diversity value of 0.53. The results of the phylogenetic analysis showed that the 30 genotypes clustered into five clusters with a similar coefficient of 0.68.